Should I stay or should I go? Explaining variation in Western jihadists’ choice between domestic and foreign fighting - Hegghammer, T (Cambridge University Press, 2013)
This article studies variation in conflict theater choice by Western jihadists in an effort to understand their motivations. Some militants attack at home, whereas others join insurgencies abroad, but few scholars have asked why they make these different choices. Using open-source data, I estimate recruit supply for each theater, foreign fighter return rates, and returnee impact on domestic terrorist activity. The tentative data indicate that jihadists prefer foreign fighting, but a minority attacks at home after being radicalized, most often through foreign fighting or contact with a veteran. Most foreign fighters do not return for domestic operations, but those who do return are more effective operatives than nonveterans. The findings have implications for our understanding of the motivations of jihadists, for assessments of the terrorist threat posed by foreign fighters, and for counterterrorism policy.